Linacs for Medical Isotope Production - A. Pramudita (Atom Indonesia, 2011)
This paper reviews efforts on using high energy (25-30 MeV) and high power (10-20 kW) electron linacs and lower energy (7 MeV) proton linacs for medical radioisotope production. Using high energy x-rays from the electron linacs, PET (Positron Emission Tomography) radioisotopes are produced through photonuclear reactions such as 19F(γ,n)18F, which also allow production of other PET radionuclides 11C, 13N, and 15O. Other mostly used medical radionuclides 99mTc can also be obtained by using the electron linacs, through photofission or photonuclear reactions. Proton linacs for PET have also been recently developed and the product has been available in the market since 2005. The linacs have been tested for 18F production. As a proton accelerator, the target systems and nuclear reactions are similar to the ones used in PET cyclotrons. Received: 01 February 2010; Revised: 05 April 2011; Accepted: 20 April 2011